Biofortification of Sodium Selenate Improves Dietary Mineral Contents and Antioxidant Capacity of Culinary Herb Microgreens - Newman, Rachel G.; Moon, Youyoun; Sams, Carl E.; Tou, Janet C.; Waterland, Nicole L. (Frontiers in Plant Science, 2021)
Selenium biofortification of plants has been suggested as a method of enhancing dietary selenium intake to prevent deficiency and chronic disease in humans while avoiding toxic levels of intake. Popular herbs such as basil (Ocimum basilicum L.), cilantro (Coriandrum sativum L.), and scallions (Allium fistulosum L.) present an opportunity for biofortification as these plants are used for added flavors to meals and are available as microgreens, young plants with increasing popularity in the consumer marketplace. In this study, basil, cilantro, and scallion microgreens were biofortified with sodium selenate in hydroponic conditions at various selenium concentrations to investigate effects on yield, selenium content, other mineral content (sodium, potassium, calcium, magnesium, phosphorus, copper, zinc, iron, manganese, sulfur, and boron), total phenol content, and antioxidant capacity (ORAC). Results showed selenium content increased significantly at all concentrations, with scallions demonstrating the largest increases. Effects on other minerals varied among herb species. Antioxidant capacity measured by ORAC and total phenol content increased in all herbs at the highest selenium treatments, but basil and scallions demonstrated decreased crop yield. Overall, these biofortified culinary herb microgreens are an ideal functional food for enhancing selenium, other dietary minerals, and antioxidants to benefit human health.